Characterization of the thyroid cancer profile of the Brazilian population between 2010 and 2019 (Research, Society and Development, 2022)
In Brazil, there is a higher incidence of thyroid neoplasms in women than men, especially in middle age. Thus, the present study aimed to evaluate thyroid cancer mortality, public investment for the hospitalization of people with this pathology, and the years of life lost by them during the period from 2010 to 2019. Through a descriptive study, with a quantitative approach, the secondary data was collected in October 2021, made available by the Department of Informatics of the Unified Health System (DATASUS), consulting the databases of the Hospital Information System (SIH) and the National Cancer Institute (INCA). Regarding the mortality rate, the increase in the incidence in women and men occurred after 40 years of age, with the age group from 70 to 79 years having the highest number of deaths. The 50-59 age group had a higher PYLL rate (potential years of life lost), based on a longevity of 80 years. The North, Northeast and South regions demanded greater financial incentives in the control of thyroid disorders. Thus, there is a need for a greater incentive to perform early exams, especially in the North, Northeast and South regions, which quantitatively require a greater application of financial resources. In addition, the high incidence rate of thyroid neoplasms in women and people over 50 years of age in Brazil reflects the need to advance health care practices.